Development of KASP markers, SNP fingerprinting and population genetic analysis of Cymbidium ensifolium (L.) Sw. germplasm resources in China - Shen, Baoming; Shen, Airong; Tan, Yun; Liu, Lina; Li, Sainan; Tan, Zhuming (Frontiers in Plant Science, 2025)
Cymbidium ensifolium (L.) Sw. is a valuable ornamental plant in the genus Cymbidium, family Orchidaceae, with high economic and ecological significance. However, the lack of population genetic information and molecular markers has hindered the development of the sales market and genetic breeding of C. ensifolium despite the abundance of commercial cultivars available. In this study, we aimed to develop a set of single nucleotide polymorphism (SNP) markers to distinguish the main cultivated C. ensifolium cultivars in China and provide technical support for domestic cultivar protection, registration, and market rights protection. A total of 1,280,516 high-quality loci were identified from 10,021,591 SNPs obtained by sequencing 50 C. ensifolium commercial cultivars using double digest restriction site-assisted DNA sequencing technology. A total of 7,599 SNPs were selected for kompetitive allele-specific PCR (KASP) primer design, and 4,360 were successfully designed as KASP markers. Population structure analysis revealed that the 50 commercial cultivars were best divided into four populations, with some correlation between the group distribution and the morphological and geographical characteristics of the germplasm. Using the genotyping results from 28 KASP markers screened from the cultivars, a minimum set of 11 markers was identified that could distinguish 83 C. ensifolium commercial cultivars completely, with the remaining 17 markers serving as extended markers. The average PIC value of the 11 markers was 0.345, which was considered medium polymorphism. DNA fingerprints were constructed for the 83 cultivars on the basis of the 11 KASP markers, providing a new approach for mapping DNA fingerprints in C. ensifolium cultivars with high efficiency, accuracy, and low cost compared with traditional methods.